Technolinguistic suspension and the digital futures of minority languages: AI and Meänkieli in Sweden - Eriksson Krutrök, Moa; Poromaa Isling, Pär (New media & society, 2025)
As AI-driven language models transform communication, minority languages like Meänkieli—a national minority language in northern Sweden—face new forms of digital marginalization. Historically suppressed by the Swedish state, Meänkieli now risks exclusion from rapidly evolving AI ecosystems. This article examines how current AI platforms shape language inclusion, combining semi-structured interviews with language technologists, conservators, and promoters, and a platform analysis of AI translation and language tools. Drawing on these materials, we develop the concept of “technolinguistic suspension” to describe the state in which Meänkieli currently exists: symbolically recognized yet excluded from the technological infrastructures that increasingly define linguistic legitimacy. We identify four interrelated aspects—two conditions (non-representative technologies and low-resource status) and two responses (active work-arounds and AI skepticism)—that illuminate how institutional neglect and platform-level dynamics jointly constrain digital revitalization. The study argues that overcoming technolinguistic suspension requires both structural reforms in platform design and sustained institutional commitment to minority language futures.